If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -10h = 2g + -12 Reorder the terms: 16 + -10h = -12 + 2g Solving 16 + -10h = -12 + 2g Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -10h = -12 + -16 + 2g Combine like terms: 16 + -16 = 0 0 + -10h = -12 + -16 + 2g -10h = -12 + -16 + 2g Combine like terms: -12 + -16 = -28 -10h = -28 + 2g Divide each side by '-10'. h = 2.8 + -0.2g Simplifying h = 2.8 + -0.2g
| 1/5n+5n=7n-18 | | -5(z-3)=-25 | | 1/5n+5n=7n-18 | | 175m-75m+53625=55000-175m | | 36-4x+6= | | -6x+-px=-z+2 | | 10x-3=-82 | | 3/4(g+7)=15 | | 48x^2-56x-24=0 | | -3(m-1)+4m=-8+9+4m | | -17-2=3+4x+5 | | 3(4z-8)=12 | | 4(v-1)=-9v+9 | | 6z-3z+5-4=3z-5+4 | | -2(d+6)-3(4d-2)=22 | | 4x-8=11y-1 | | p=5/9*350000 | | -4(x-4)=28+8x | | 2g-12=16-10h | | 13.50/3 | | -45-5+2b=10 | | 175m-75m-53625=55000-175m | | -12x-3x=-8 | | Z=6x+px+2 | | 4x-45=7(x-9) | | -(4-6n)=n+11 | | B-1/2=b/3+7 | | ((7x+6)(2x+10))/((6x+2)(7x+5)) | | y=6/7x-2 | | -7+14k-13+-(-5k)+3= | | x/-8=-1-(-3) | | 3x=3(8-7x) |